Cost Effectiveness of Cochlear Implantation in Single-Sided Deafness. Issue 8 (25th September 2021) - Dreyfuss, Michael; Giat, Yahel; Veraguth, Dorothe; Röösli, Christof; Huber, Alexander M.; Laske, Roman D.
Abstract : Objective: To analyze the cost effectiveness of cochlear implantation (CI) for the treatment of single-sided deafness (SSD). Study Design: Cost-utility analysis in an adapted Markov model. Setting: Adults with single-sided deafness in a high-income country. Intervention: Unilateral CI was compared with no intervention. Main Outcome Measure: Incremental cost-effectiveness ratios were compared with different cost-effectiveness thresholds ($10, 000 to $150, 000) for different age, sex, and cost combinations. The calculations were based on the quality-adjusted life year (QALY), national life expectancy tables, and different cost settings. The health utility values for the QALY were either directly collected from published data, or, derived from published data using a regression model of multiple utility indices (regression estimate). Results: The regression estimate showed an increase of the health utility value from 0.62 to 0.74 for SSD patients who underwent CI. CI for SSD was cost effective for women up to 64 years ($50, 000 per-QALY threshold), 80 years ($100, 000 per-QALY threshold), and 86 years ($150, 000 per-QALY threshold). For men, these values were 58, 77, and 84, respectively. Changing the discount rate by up to 5% further increased the cutoff ages up to 5 years. A detailed cost and age sensitivity analysis is presented and allows testing for cost effectiveness in local settings worldwide. Conclusions: CI is a cost-effective option to treat patients with SSD.